Neuro-Behçet's disease mimicking a cranial tumour. (21st June 2015) - Senol, Serkan; Ucar, Mehmet; İmamoğlu, Hakan and Yildirim, Afra
Abstract : Behçet's disease affects many systems and has been described as a multisystem disorder. In Behçet's disease, neurological involvement is responsible for morbidity and mortality, and can sometimes mimic other neurological disorders. We present a case of neuro-Behçet's disease that mimicked a cranial tumour.